Modification of the implementation of the underexcitation limiter within the generator excitation system of unit B1 at TPP “Nikola Tesla B” - Klasnić, Ilija G; Veinović, Slavko; Joksimović, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
The paper describes the event of the outage of the unit B1 at TPP "Nikola Tesla B" from the grid which, as well as the modification of the implementation of the underexcitation limiter within the excitation system, which is the result of a detailed analysis of the excitation system response immediately before and during the event itself. The structure of the underexcitation multiple-segment straight-line characteristic and the method of its realization are described. The modification of the implementation of the limiter was carried out based on the recordings of unit B1 outage from the grid and in-depth analysis of the event and the response of the excitation system, Additionally, the measurements that enter the limiter implementation algorithm are filtered: stator voltage measurement and generator active power measurement. The limiter also has a variable gain depending on the range of reactive power or active segment. Lastly, the results of testing the response of the underexcitation limiter during the operation of the generator B1 on the grid are presented, which indicate a stable response with damped oscillations.